Dichotic listening impairments in early onset schizophrenia are associated with reduced left temporal lobe volume - Collinson, S; Mackay, C; Jiaqing, O; James, A; Crow, T (Elsevier, 2009)
Dichotic listening (DL) impairments, inparticular the loss or reduction of right ear advantage (REA) in people with schizophrenia have been variously interpreted as both a state and trait marker for schizophrenia. To date, there has been no comprehensive investigation of dichotic language impairments in relation to the structural integrity of the temporal cortex - the likely neural substrate for such impairments. In this study of 39 early onset patients and matched controls we used a dichotic listening procedure and examined the findings in relation toMRImeasurements of gross and regional cerebral volumes. No overall group difference in ear advantage was found between patients and controls but patients who showed absence of REA also demonstrated an accompanying reduction of left temporal lobe volume compared with patients who showed normal ear advantage and controls. The findings suggest that impaired DL performance is a correlate of structural change in the temporal lobe and that this is apparent in early onset cases.